2015
DOI: 10.1063/1.4913977
|View full text |Cite
|
Sign up to set email alerts
|

The externally corrected coupled cluster approach with four- and five-body clusters from the CASSCF wave function

Abstract: An externally corrected CCSDt (coupled cluster with singles, doubles, and active triples) approach employing four- and five-body clusters from the complete active space self-consistent field (CASSCF) wave function (denoted as ecCCSDt-CASSCF) is presented. The quadruple and quintuple excitation amplitudes within the active space are extracted from the CASSCF wave function and then fed into the CCSDt-like equations, which can be solved in an iterative way as the standard CCSDt equations. With a size-extensive CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 104 publications
1
16
0
Order By: Relevance
“…The major breakthrough in the understanding of the superb performance of the ACP-D45 approach in a strongly correlated regime came in 1984 [125], followed by two other key articles published in 1991 [64] and 1996 [126]. By performing cluster analysis [124] of the PUHF wave function within the orthogonally spin-adapted framework, in which the PUHF state was assumed to be exact, and using the philosophy of the externally corrected CC methods [125,126,161,[198][199][200][201][202][203][204][205][206][207][208][209], the authors of Refs. [125,126] demonstrated that the T 4 cluster component extracted from PUHF with the help of the Thouless theorem and read into the CCD system, Eq.…”
Section: A Overview Of the Acp Schemesmentioning
confidence: 99%
“…The major breakthrough in the understanding of the superb performance of the ACP-D45 approach in a strongly correlated regime came in 1984 [125], followed by two other key articles published in 1991 [64] and 1996 [126]. By performing cluster analysis [124] of the PUHF wave function within the orthogonally spin-adapted framework, in which the PUHF state was assumed to be exact, and using the philosophy of the externally corrected CC methods [125,126,161,[198][199][200][201][202][203][204][205][206][207][208][209], the authors of Refs. [125,126] demonstrated that the T 4 cluster component extracted from PUHF with the help of the Thouless theorem and read into the CCD system, Eq.…”
Section: A Overview Of the Acp Schemesmentioning
confidence: 99%
“…The ecCCSD method has a long history and external sources, ranging from unrestricted Hartree-Fock [86][87][88][89] to CASSCF and CASCI [90][91][92][93][94] and, most recently, full configuration interaction quantum Monte Carlo, 95 have been used. One of the more successful applications of ecCCSD is the reduced multireference (RMR) CCSD method, 96,97 which uses a MRCISD wave function as the external source.…”
Section: Introductionmentioning
confidence: 99%
“…The ecCCSD method has a long history and external sources, ranging from unrestricted Hartree-Fock [86][87][88][89] to CASSCF and CASCI [90][91][92][93][94] and, most recently, full configuration interaction quantum Monte Carlo, 95 have been used. One of the more successful applications of ecCCSD is the reduced multireference (RMR) CCSD method, 96,97 which uses a MRCISD wave function as the external source.…”
Section: Introductionmentioning
confidence: 99%